Perancangan Interior Café, Record Store dan Mini Cinema Bergaya Retro Industrial di Jakarta - Grace Mellyana Chiong; Stephanus P Honggowidjaja (Intra, 2016)
Listening to music is a form of entertainment that can be enjoyed whenever and wherever using various means, one of which is vinyl record. In comparison to other musical medias, vinyl record comes with a multitude of benefits, such as clarity and sound precision, so nowadays vinyl records are gaining more attentions from the mass, both local and international. However, there has yet to exist a proper vinyl record store in Indonesia. In addition to music, film and cafe are another popular example of entertainments that can easily be found in Jakarta. Nonetheless, cinemas dedicated to old movies as well as cafes with old style interior that accompanied by music played directly from vinyl records are still hard to find, if not impossible. With that in mind, a cafe, record store, and mini cinema is designed in order to provide the necessary facility that could embrace the said demands. The design takes inspiration from the industrial and retro style, with an eco interior (refunction) approach using container, wood pallets, used wood crate that is still in good condition as a few elements of the interior. This combination are expected to produce a unique and exquisite design.